Structural and antigenic stability of H5N1 hemagglutinin trimer upon release from polyanhydride nanoparticles. Issue 11 (4th February 2014) - Ross, Kathleen A.; Loyd, Hyelee; Wu, Wuwei; Huntimer, Lucas; Wannemuehler, Michael J.; Carpenter, Susan; Narasimhan, Balaji
Abstract Although H5N1 avian influenza has not yet acquired the capacity to readily infect humans, should it do so, this viral pathogen would present an increasing threat to the immunologically naïve human population. Subunit vaccines based on the viral glycoprotein hemagglutinin (HA) can provide protective immunity against influenza. Polyanhydride nanoparticles have been shown to enhance efficacy of subunit vaccines, providing the dual advantages of adjuvanticity and sustained delivery resulting in enhanced protein stability and immunogenicity. In this work, a recombinant trimer of H5 (H53) was encapsulated and released from polyanhydride nanoparticles. Release kinetics of the encapsulated H53 were found to be dependent on polymer chemistry (i.e., hydrophobicity and molecular weight). Polyanhydride nanoparticles composed of sebacic anhydride and 1, 6‐bis(p‐carboxyphenoxy)hexane (CPH; that degrade into more acidic monomers) released structurally stable HA H53, while H53 released from formulations composed of CPH and 1, 8‐bis(p‐carboxyphenoxy)−3, 6‐dioxaoctane (CPTEG) (that are amphiphilic and whose degradation products are less acidic) displayed unfolding of tertiary structure. However, the antigenicity of the H53 based on binding of a H5‐specific monoclonal antibody was preserved upon release from all the formulations studied, demonstrating the value of polyanhydride nanoparticles as a viable platform for HA‐based influenza vaccines. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4161–4168, 2014.